A Review on 3D printed force sensors. Issue 1 (March 2021) - Choudhary, H; Vaithiyanathan, D.; Kumar, H
Abstract: A force sensor plays major role in robotics, wearable electronics and meteorological applications. Three dimensional (3D) printing is an exceptional technology and provides easy and economical fabrication process for the force sensors. Some salient features of 3D printing and development of force sensors in recent times have been represented in this paper. All possible forms of force sensors, for instance flexible, transparent, stretchable and highly sensitive can be developed using 3D printing technologies in an economical, quick and environmental-friendly approach. Over the years, fused deposition modeling (FDM) is gaining attention for the fabrication of force sensors. Also, due to advancements in materials and fabrication process, these sensors are being developed with enormous benefits. Some recent developments include flexible capacitive force sensor, wearable sensor and tactile sensor that are popular with 3D printing.